2005
DOI: 10.1111/j.1570-7458.2005.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

An improved method to determine the biological activity (LC50) of the granulovirus PoGV in its host Phthorimaea operculella

Abstract: Granulovirus (PoGV) is a promising candidate to substitute for chemical insecticides in integrated pest management (IPM) of the potato tuber moth, Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae). A procedure to assess pathogenicity (LC50) and its standardization is crucial for research into the use of pathogens as biocontrol agents. In the present study, an egg‐dip bioassay method was developed and its precision tested in a series of six bioassays over a time period of 18 months. Bioassays were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 17 publications
2
21
0
2
Order By: Relevance
“…The virus was propagated through submersion of surface-perforated tubers (tuber-dip method) and through submersion of sheet of paper containing eggs (egg-dip method) into a virus suspension for 2 and 1 min, respectively, to promote contamination (Reed and Springett 1971;Sporleder et al 2005). Virus suspension was made of ten last-instar infected larvae per litre of water with 0.1% Tween Ò 20 (polyoxyethylene sorbitan monolaurate) (Oxiteno S/A, São Paulo, Brazil), according to the protocol of CIP (International Potato Center 1992).…”
Section: Insect Origin and Virus Isolatementioning
confidence: 99%
“…The virus was propagated through submersion of surface-perforated tubers (tuber-dip method) and through submersion of sheet of paper containing eggs (egg-dip method) into a virus suspension for 2 and 1 min, respectively, to promote contamination (Reed and Springett 1971;Sporleder et al 2005). Virus suspension was made of ten last-instar infected larvae per litre of water with 0.1% Tween Ò 20 (polyoxyethylene sorbitan monolaurate) (Oxiteno S/A, São Paulo, Brazil), according to the protocol of CIP (International Potato Center 1992).…”
Section: Insect Origin and Virus Isolatementioning
confidence: 99%
“…To describe the nematicidal effects of the compounds against B. xylophilus, the median lethal concentrations (LC 50 ) were calculated according to probit analysis (Sporleder et al, 2005). Regression analyses were also carried out by SPSS for linear model.…”
Section: Discussionmentioning
confidence: 99%
“…However, microbial control of P. operculella is not yet developed for massive commercial use although some authors have indicated the potential use of those pathogens in the future (Lacey and Arthurs 2005;Arthurs et al 2008). In fact, some small scale tuberworm control by microbes has been already used successfully (Kroschel et al 1996a, b;Sporleder et al 2001Sporleder et al , 2005Sporleder 2003).…”
Section: Parasitoids and Predatorsmentioning
confidence: 99%
“…Timing of virus applications (Briese 1981;Briese and Mende 1981). Timing of virus applications (Reed 1971;Reed and Springett 1971), methods of application, concentration, and ultraviolet radiation can influence effectiveness of control (Kroschel et al 1996a, b;Sporleder et al 2001Sporleder et al , 2005Sporleder 2003).…”
Section: Parasitoids and Predatorsmentioning
confidence: 99%